Efisiensi Pemasaran Air Nira Lontar Di Desa Hendrosari Kecamatan Menganti Kabupaten Gresik - Putriani, Adellia; Kurniasari, Dwiyana Anela (AGRI-SOSIOEKONOMI, 2023)
This study aims to analyze the level of efficiency in marketing palm sap water by identifying marketing channels and analyzing the amount of marketing margin and farmer's share of palm sap water in Hendrosari Village, Menganti District, Gresik Regency. The data used in this study are primary data and secondary data. Primary data was obtained based on the results of interviews conducted by distributing questionnaires to farmers and marketing agencies. Secondary data comes from the Office of the Head of Hendrosari Village and the official website of Hendrosari Village. Samples of palm sap water farmers were taken using simple random sampling method, while marketing agencies used purposive sampling method. The results showed that marketing of palm sap water in the study area consisted of two marketing channels, the marketing margin obtained in marketing channel I was Rp0, and on the marketing channel II, namely Rp4000. The farmer's share value in marketing channel I is 100%, and marketing channel II is 80.95%. The value of marketing efficiency I is 7.63% <50% which means that marketing channel I is an efficient marketing channel. Marketing channel II is 12.49% <50% which means that marketing channel II is an efficient marketing channel. It can be concluded that from the type of marketing channel used by water palm sap farmers in Hendrosari Village, it shows that marketing channel I is the most efficient channel compared to marketing channel II.